Analisis Penerapan Sistem Informasi Manajemen Rumah Sakit (SIMRS) Khanza Terhadap Efektivitas Pendapatan Rumah Sakit Ibu Dan Anak Permata Hati Mataram - Dini Sartika; I Made Krisna Ardika; Nur Fitriyah (Jurnal Riset Mahasiswa Akuntansi, 2026)
This study aims to analyze the effect of implementing the Hospital Management Information System (SIMRS) KHANZA on the revenue effectiveness of Permata Hati Mother and Child Hospital, Mataram. The research adopts a quantitative approach using a survey method with a cross-sectional design. The research population includes all employees directly involved in the use of SIMRS and the hospital revenue management process, totaling 274 employees. The sampling technique applied is probability sampling using the Slovin formula, resulting in a sample of 73 respondents. Data were collected through an online questionnaire based on a Likert scale. The data analysis methods employed consist of validity testing, reliability testing, classical assumption tests, and simple linear regression analysis using SPSS software. The results indicate that the implementation of SIMRS KHANZA has a positive and significant effect on hospital revenue effectiveness. These findings suggest that the optimal utilization of SIMRS enhances the orderliness of service recording, improves the accuracy of billing processes, and supports the smooth management of the hospital revenue cycle. Therefore, SIMRS KHANZA serves as a strategic instrument in supporting effective revenue management and the financial sustainability of the hospital.